Exercise blood pressure and cardiac structure: A systematic review and meta-analysis of cross-sectional studies. Issue 9 (September 2021) - Moore, Myles N.; Climie, Rachel E.; Otahal, Petr; Sharman, James E.; Schultz, Martin G.
Abstract: Objectives: A hypertensive response to exercise (HRE) is associated with cardiovascular disease and high blood pressure (BP). Sub-clinical changes to cardiac structure may underlie these associations, although this has not been systematically determined. Via systematic review and meta-analysis, we aimed to (1) assess the relationship between exercise BP and cardiac structure, and (2) determine if cardiac structure is altered in those with an HRE, across various study populations (including those with/without high BP at rest). Design and methods: Three online databases were searched for cross-sectional studies reporting exercise BP, HRE and cardiac structural variables. Random-effects meta-analyses and meta-regressions were used to calculate pooled correlations between exercise BP and cardiac structure, and pooled mean differences and relative risk between those with/without an HRE. Results: Forty-nine studies, (n = 23, 707 total; aged 44 ± 4 years; 63% male) were included. Exercise systolic BP was associated with increased left ventricular (LV) mass, LV mass index, relative wall thickness, posterior wall thickness and interventricular septal thickness (p < 0.05 all). Those with an HRE had higher risk of LV hypertrophy (relative risk: 2.6 [1.85–3.70]), increased LV mass (47 ± 7 g), LV mass index (7 ± 2 g/m 2 ), relative wall thickness (0.02 ± 0.005), posterior wall thickness (0.78 ± 0.20 mm), interventricular septal thickness (0.78 ± 0.17 mm) and left atrial diameter (2 ± 0.52 mm) vs. those without an HRE (p < 0.05 all). Results were broadly similar between studies with different population characteristics. Conclusions: Exercise systolic BP is associated with cardiac structure, and those with an HRE show evidence towards adverse remodelling. Results were similar across different study populations, highlighting the hypertension-related cardiovascular risk associated with an HRE.